Form-stable electrospun nanofibrous mats as a potential phase change material - KAHRAMAN, MEMET VEZİR (TAYLOR & FRANCIS INC, 2019)
A series of Poly vinyl butyral-Poly (acrylic acid) (PVB-PAA) based form-stable phase change materials (PCMs) have been prepared for the use of thermal energy storage applications. Six types of formulations containing five different fatty alcohols were prepared by adding PVB to PAA. Using electrospinning to fabricate nanofibrous mats, our aim was to investigate their properties as form-stable PCMs. Fatty alcohols, 1-Tetradecanol, 1-Hexadecanol, 1-Octadecanol, 1-Eicosanol and 1-Docosanol, were added separately to base formulation. The structural characterization tests were performed by ATR-FTIR spectroscopy. Morphological tests were conducted using Scanning Electron Microscope (SEM). Thermal performances and phase change behaviors were tested by thermogravimetric analysis system (TGA) and differential scanning calorimetry (DSC). The heating cycle phase change enthalpy is measured between 223 and 241 J/g, and the freezing cycle phase change enthalpy is found between 215 and 239 J/g. The main decomposition PVB-PAA based PCMs started at 220 degrees C. This study suggested that PVB-PAA based PCMs possess well phase change properties and they were found to have an applicable temperature range. With the presented results these materials promise a great potential in thermal energy storage applications.
Keywords: Phase change material; form-stable; thermal energy storage; electrospinning; nanofibrous mats; FATTY-ACID EUTECTICS; COMPOSITE FIBERS; TEREPHTHALATE COMPOSITE; STRUCTURAL MORPHOLOGY; THERMAL PERFORMANCE; FABRICATION; STORAGE; IMMOBILIZATION; RETRIEVAL